Beberapa Model Integrasi Sains dan Islam serta Implikasinya terhadap Pendidkan Islam - Isran Bidin; Mas`ud Zein Zein; Rian Vebrianto (Bedelau: Journal of Education and Learning, 2020)
The dichotomy of education had resulted in an output crisis that is materialistic, individualistic, and the lack of spirituality. Therefore, reconstruction in the implementation of education was needed in the form of integrating science and Islamic values ​​to become the veins of organizing education in all institutions, especially those labeled as Islamic institutions. This research aimed to explore several models of the integration of science and Islam and its implications for Islamic education. This research used a journal meta-analysis approach. The data source was taken from 15 selected online journals. The different models found in this research required a further discussion to continue to renew the thinking of the fields of integration of science and Islam. This effort is expected to bring about the compatibility of activities in the field of education with the current development and its acceleration of science and technology.